Methodological proposal for software development in degree projects in the specialty of Computer Systems Engineering - Moreira Pinargote, Freddy Adrian; Chancay Giler, José Eduardo; Pinargote Navarrete, Carlos Luis; Cruz Felipe, Marely del Rosario (IJERI: International Journal of Educational Research and Innovation, 2019)
The objective of this paper is to propose a software development methodology for the degree works in the specialty of Computer Systems Engineering, through analytical and investigative study. Interview techniques were applied to a group of software developers, and the survey technique was applied, which was applied to students and teachers of the Faculty of Computer Science. Which allowed to collect certain characteristics of the existing methodologies, in such a way that they are adaptable and easy to execute for the scenario that is handled in the career and the knowledge that the students have when using a methodology of development in their projects. As a result of the work, a hybrid methodology called XPRUM is presented, which consists of four phases, which integrates the XP and Scrum methodology, which allows to conduct the software development process in the titration works. Promoting the use of the tool presented by the Kanban Methodology, which allows the control of processes and their activities.